A tale of two walls a comparison of the Green Wall projects in Inner Mongolia and the Sahelo-Saharan Regions - Ratilla, Daniel Chen (Budhi: a Journal of Ideas and Culture, 2019)
Desertification as a bio-physical stressor threatens food and water security and is exacerbated by climate change. Other issues such as peace, gender equity, and livelihood are some examples of socio-economic issues also connected desertification. This is apparent in the cases of Inner Mongolia and the Sahelo-Saharan region, where desertification has spurred the creation of afforestation projects, colloquially known as "Green Walls": these are the Three-North Shelterbelt Project, and the Great Green Wall of the Sahara and the Sahel Initiative, respectively. This paper explores the principles of environmental ethics (such as vulnerability, common goods, biological and cultural diversity, and the environmental virtues) in the two Green Wall projects and compares these in their respective environmental management strategies. The paper concludes that both Green Wall projects can benefit from collaboration such as an exchange of knowledge and effective methods and practices. These include the capacity of the Chinese State in resource mobilization and of the African Union's emphasis on organization at the grassroots level.